Maternal and foetal outcome of pregnancy in women with connective tissue diseases - Klimaszyk, Katarzyna; Wender-Ożegowska, Ewa; Kędzia, Małgorzata (Journal of Medical Science, 2021)
Introduction. The majority of patients diagnosed with systemic connective tissue diseases are women of childbearing age.Aim. The analysis of obstetric results and exacerbation rates in the pregnancies involving systemic connective tissue diseases.Material and Methods. We retrospectively reviewed perinatal outcomes of fourteen women with systemic connective tissue diseases hospitalised in the Department of Reproduction in the period between September 2019 and July 2021.Results. Median duration of a pregnancy was 37 weeks. One pregnancy ended in a stillbirth in week 28. Of the 13 live births, preterm delivery occurred in 5 cases. Of the 13 live-birth neonates, preterm delivery occurred in five cases. The Caesarean section rate was 57.1% and vaginal delivery rate was 42.9%. The mean birth weight of the live neonates was 2787g (SD 892), and the median Apgar score in the 1st and the 3rd minute was 10.In total, all 4 patients with the active disease at the time of conception and 1 who did not decide to undergo the recommended mitral valve surgery prior to pregnancy experienced symptoms indicating a disease flare-up in the course of pregnancy. None of the patients who planned their pregnancy experienced an exacerbation of the disease.Conclusions. All patients diagnosed with systemic connective tissue diseases should receive multidisciplinary care prior to conception, during pregnancy and in the postpartum period. Furthermore, they should be monitored by a team of specialists, due to the risk of a disease exacerbation and high rates of maternal and foetal complications resulting from the underlying condition.